Inclusive Empowerment of BUMDes Program : Evaluation of Participation and Accessibility for Vulnerable Groups in Daha Utara District - Rusdi Rusdi; Ika Devi Pramudiana; Ferry Ramadhan; Sri Kamariyah (Perspektif Administrasi Publik dan hukum, 2025)
Inclusive empowerment is a village development approach that emphasizes the active involvement of vulnerable groups—such as women, the elderly, people with disabilities , and the poor—in all stages of planning through to evaluation. This study aims to evaluate the implementation of the Village-Owned Enterprises ( BUMDes ) program in Daha Utara District, South Kalimantan, in ensuring participation and accessibility for these groups. Using a qualitative descriptive approach, data were collected through interviews with BUMDes managers and representatives of vulnerable groups. The evaluation was conducted based on William N. Dunn's six policy indicators: effectiveness, efficiency, adequacy, fairness, responsiveness , and accuracy. The results show that the BUMDes program has had a limited positive impact on increasing the income of vulnerable groups, but their involvement is still limited, both in terms of participation and physical access. The main challenges include the lack of disability- friendly infrastructure , minimal capacity training, and community resistance due to low program transparency. On the other hand, local cultural support such as mutual cooperation, involvement of traditional leaders, and partnerships with the village government are important supporting factors. This study recommends increasing human resource capacity, strengthening inclusive infrastructure, socialization based on local wisdom, and adaptive digitalization to expand access. With strategic intervention, BUMDes is expected to be able to transform into a driving force for fair, participatory and sustainable village development.